2004
DOI: 10.1007/s00330-004-2250-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing accuracy of CT-guided percutaneous biopsies of pulmonary lesions

Abstract: The purpose of this study was to evaluate the performance and complication rate of CT-guided percutaneous lung biopsy of pulmonary lesions using a coaxial automated biopsy device and to determine factors influencing the false negative rate for the diagnosis of malignancy. A prospective study of 605 consecutive biopsies performed in 595 patients was undertaken. The performances for the diagnosis of malignancy, for the specific diagnosis of benignity and the complication rate were calculated. Patients' character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
74
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 17 publications
12
74
1
3
Order By: Relevance
“…To our knowledge, there are only few studies on transthoracic biopsy using FNA and non-coaxial technique in recent literature (11,12). Table 5 summarizes some of the previous studies performed by other investigators (2,4,5,9,10,14,15). In the present study, the diagnostic accuracy was 97.6%, with 97.3% sensitivity and 100% specificity for malignant disease.…”
Section: Discussionsupporting
confidence: 46%
“…To our knowledge, there are only few studies on transthoracic biopsy using FNA and non-coaxial technique in recent literature (11,12). Table 5 summarizes some of the previous studies performed by other investigators (2,4,5,9,10,14,15). In the present study, the diagnostic accuracy was 97.6%, with 97.3% sensitivity and 100% specificity for malignant disease.…”
Section: Discussionsupporting
confidence: 46%
“…The sensitivity of lung biopsy in this study was 90.4%, which is comparable to other studies [3][4][5]11]. This high sensitivity adds support to the efficacy of CT-guided needle biopsy for evaluation of pulmonary nodules in the presence of on-site cytologist.…”
Section: Discussionsupporting
confidence: 84%
“…Percutaneous CTguided needle lung biopsy has a high diagnostic accuracy and is a well-established procedure for obtaining a cytological evaluation of pulmonary nodules [2,3]. Factors affecting diagnostic accuracy are lesion size, immediate on-site sample evaluation by a cytologist, and technique, including type of biopsy device [4][5][6][7][8][9][10]. A previous study has shown core biopsies to be a more accurate method of tissue sampling without increasing risk of complications when compared to fine-needle aspiration [11].…”
Section: Introductionmentioning
confidence: 99%
“…El tamaño lesional es un factor importante y ampliamente estudiado, con una menor sensibilidad de la técnica reportada en lesiones menores a 15 mm y mayores a 5 cm, estas últimas por un mayor porcentaje de necrosis asociada 6,19 . En nuestro estudio no observamos una relación entre el tamaño de la lesión y el rendimiento de la técnica, probablemente por el bajo porcentaje de lesiones menores a 20 mm.…”
Section: Discussionunclassified